Oral enzyme combination therapy reduces systemic inflammation, urinary CTXII and pain in knee osteoarthritis: a proof-of-mechanism, randomised, crossover, double-blind, placebo-controlled trial - Thomas Pap; Odd Erik Johansen; Yves Henrotin; Valérie Badot; Stefanie Rau; Maximilian von Eynatten; Jean-Emile Dubuc; Siddhartha Lieten; Didier Urbin-Choffray; Karl Brabants (RMD Open)
Objectives Oral enzyme combination (OEC) therapy with bromelain, trypsin and rutoside reduces pain and improves function in patients with knee osteoarthritis (OA). Here, we investigated several potential biological mechanisms underlying the clinical effects of OEC therapy in patients with established knee OA with respect to innate immunity, systemic inflammation and cartilage turnover (EudraCT 2020-003154-80, NCT05038410).Methods Patients (age ≥40 years, body mass index (BMI) ≤35 kg/m2) with symptomatic knee OA were randomised to either placebo or OEC, administered 2×3 tablets/day, for 8 weeks before crossing over after a 4-week washout period. Different markers exploring innate immunity, inflammation and cartilage matrix degradation have been measured in the blood using immunoassays or cytometric methods. Data from the modified intention-to-treat population (mITT) were analysed using a generalised linear mixed model. No correction for multiple comparisons was made due to the exploratory nature of the study.Results Altogether, 45 patients were randomised; 43 completed both treatment sequences (mITT; mean age: 63.3 years; mean BMI: 27.4 kg/m2; mean global Knee injury and Osteoarthritis Outcome Score (KOOS): 48.7). OEC significantly increased levels of α2-macroglobulin (p=0.038) and interleukin-10 (p<0.0001) while decreasing urinary carboxyl-terminal cross-linked telopeptide of type II collagen (p=0.038). Patients administered OEC exhibited significant improvements in KOOS Pain (p=0.0464) and Symptoms (p=0.026) subdomains but not globally. OEC was well tolerated, with no serious related adverse events reported in either group.Conclusions One of the key findings of this proof-of-mechanism study is that OEC modulates IL-10 production, suggesting an anti-inflammatory effect in patients with knee OA. This main finding contributes to explaining the effects of OEC on pain and function in these patients.Trial registration number NCT05038410.